Ngabungbang Ritual Culture in Peasant Communities - Irwansyah, Shindu; Nuramin, Hadi; Wahyudin, Dede (International Journal of Islamic Khazanah, 2020)
The purpose of this study is to explore the purpose of carrying out the rituals of ngabungbang and increase the local wisdom of Sundanese people, especially the people of Cihideung. This research uses descriptive qualitative methods, data collection techniques used are observation, interviews, document studies, literature studies, namely by investigating and covering the analysis and interpretation of data to conclusions based on research. Humans basically have bad traits which must be cleaned in order to bring kindness, peace and comfort to other beings. Cihideung residents believe that spirits and spirits who occupy their place can give good or bad. ngabungbang is silent outside the building by staying up all night especially in the sacred place of the full moon calendar which is usually done on the fourteenth of the month of mulud because in this month the birth of the prophet Muhammad SAW. the mosque. The mourning ritual is still carried on from generation to generation which mediates the people of Cihideung to rid themselves of bad traits, stay away from reinforcements in order to get good and be kept away from the ugliness that befalls them when living life, and respect their spirits with media used as media symbol in ritual. The media in this ritual are offerings for the karuhun which consist of: Gapar mulud, Gapar Kabulan, Nyimbel Red and white porridge, bitter coffee, brown sugar, milk, and clear water, salt, rice cone, rice and money.